Cryptic genetic structure within Valentin's Lizard, Darevskia valentini (Boettger, 1892) (Squamata, Lacertidae), with implications for systematics and origins of parthenogenesis. Issue 7 (3rd October 2021) - Candan, Kamil; Kornilios, Panagiotis; Ayaz, DinÇer; Kumlutaş, Yusuf; GüL, Serkan; Caynak, Elif Yildirim; Ilgaz, Çetin
Abstract : Taxonomy of the lacertid genus Darevskia has been complex since the first morphology-based studies. Darevskia valentini, mostly distributed in Turkey, currently includes three subspecies, but its interspecific and intraspecific taxonomic status has so far been shaped only by morphological evaluations, without molecular phylogenetic assessments. In this study, samples from the entire distribution of this species and its closest relatives were evaluated with molecular phylogenetic analyses of a multi-marker dataset, comprised of maternally-inherited mitochondrial and biparentally-inherited nuclear markers. We discovered two previously unrecognized genetically highly divergent lineages. The distinction of these two lineages is supported by gene trees, haplotype networks, divergence time estimation and species-delimitation analyses. We discuss possible taxonomic resolutions given that the phylogenies do not seem to agree with currently accepted taxonomy. Our results advance the knowledge of the ancestry of parthenogenesis as a result of past hybridization events between parental species pairs, because the paternal origin of some parthenogenetic species lies within the new lineages discovered here.